1969
DOI: 10.1126/science.163.3872.1209
|View full text |Cite
|
Sign up to set email alerts
|

Plant Injury by Air Pollutants: Influence of Humidity on Stomatal Apertures and Plant Response to Ozone

Abstract: Ozone injury to Bel W3 tobacco and pinto bean plants increases with increasing humidity. The degree of plant injury sustained correlates well with porometer measurements; this indicates that the size of stomatal apertures increases with increasing humidity. Humidity may therefore influence plant response to all pollutants and may account in part for the greater sensitivity of plants to ozone-type injury in the eastern United States compared with the same species of plants grown in the Southwest. with those gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 1 publication
2
13
0
Order By: Relevance
“…8 - 9 The present study confirms that at low relative humidities the stomatal resistance to gaseous diffusion is greater in both the bean and tobacco plants, but, in addition, the lower injury observed in the dry atmosphere may be compounded by the greater degree of closure during ozonation, particularly in the resistant cultivars. Such an interaction between stomatal aperture and atmospheric humidity when the gaseous pollutant sulfur dioxide is present has been observed by Mansfield and Majernik.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…8 - 9 The present study confirms that at low relative humidities the stomatal resistance to gaseous diffusion is greater in both the bean and tobacco plants, but, in addition, the lower injury observed in the dry atmosphere may be compounded by the greater degree of closure during ozonation, particularly in the resistant cultivars. Such an interaction between stomatal aperture and atmospheric humidity when the gaseous pollutant sulfur dioxide is present has been observed by Mansfield and Majernik.…”
Section: Discussionsupporting
confidence: 72%
“…Atmospheric humidity has also been observed to alter the response of plants to O 3 ; at low relative humidities O3 injury was less than at high humidities in a range of plant species. 8 ' 9 Permeability studies suggested that the reduced injury was attributable to decreased stomatal apertures at the low humidities. For plants to be useful in cleaning the atmosphere of O 3 the stomata must remain open in the presence of O3.…”
Section: Importance Of Moisture On Stomatal Behavior Of Plants Subjecmentioning
confidence: 99%
“…ln the current study, tbe increase in visible injury witb decreasing VPD was probably a result of an increase in stomatal conductance at low VPDs (Grantz & Zeiger, 1986;Assmann & Gershenson, 1991;Kappen & Haeger, 1991). Other species sucb as Bel W3 tobacco and Pinto beans (Otto & Daines, 1969), and Lycopersicon esculentum (Mortensen, 1992) sbowed a similar response to changes in VPD.…”
Section: Predictions From the Neural Networkmentioning
confidence: 61%
“…Depending on the change in Ψ in dry conditions, g s can be reduced, possibly protecting plants from effects of O $ by reducing O $ uptake (Otto & Daines, 1969 ;Tingey & Hogsett, 1985 ;Reiner et al, 1996). A direct relationship between g s and the reduction in final plant mass due to high O $ has been observed (Volin et al, 1998).…”
Section: Leaf Injury Related To Irrigationmentioning
confidence: 99%